MANAJEMEN KURIKULUM DALAM PERSPEKTIF BEAUCHAMP - Izzatul Fitriyah (Universitas Nurul Jadid, 2021)
Curriculum management is a curriculum management system that is cooperative, understood, systemic and systematic to achieve curriculum goals. A good curriculum is a curriculum that follows the development of community-based science and technology. Curriculum management determines success and failure in education. Therefore, the responsibility of educational institutions and all education stakeholders must have the same vision in planning, organizing, implementing and evaluating curriculum. And in the higher education curriculum management dimension, to ensure that the adoption or implementation of a well-designed curriculum model that can be continued according to plan, management readiness and organizational behavior are needed to ensure smooth implementation, coherence between curriculum and learning. also needed in educational institutions. First, the curriculum rests on curriculum goals or objectives - the curriculum goals to be achieved. When the curriculum is conceptualized as a development tool for students' reflective thinking (the development of reflective thinking on the part of students), the curriculum must be interpreted as a development tool to reflect reflective young people. Likewise, when the curriculum is conceptualized as transmitting cultural heritage, the curriculum must be interpreted as an instrument to attach cultural heritage to the next young generation. Second, the curriculum is based on the point of view based on the context of the curriculum used.